SOCIAL INEQUALITIES: PROBLEMATIKA STRATEGI PENGEMBANGAN DAKWAH DALAM PERSPEKTIF TEORI SOSIAL KONFLIK - Sulkhan Chakim (Komunika, 2015)
Social inequalities is the factured identities in social life, can be explained from the perspective of social-conflict theory as an inequality in resource access control in social life, which is caused by various sources, namely the existence of social class, gender, religion, geographical location, race/ethnicity and others. Various sources of social inequality should be used as a base framework for the development strategy by activists proselytizing mission, so the goal can be achieved embodiment Khaira Ummah. In this study, the formulation of development strategy of the Islamic da'wah refers amar ma'ruf nahi munkar in the formulation of social reengineering